Corrosion polarization behavior and microstructural analysis of AA1070 aluminium silicon carbide matrix composites in acid chloride concentrations. Issue 1 (1st January 2017) - Loto, Roland Tolulope; Babalola, Philip
Abstract: The effect of SiC content and NaCl concentration on the corrosion resistance of AA1070 aluminium in 2 M H2 SO4 was evaluated with potentiodynamic polarization technique, open circuit potential measurement (OCP) and optical microscopy. Results showed SiC increased the corrosion susceptibility of the alloy at lower NaCl concentrations compared to results obtained at 0% NaCl which showed significant decrease in corrosion rates, with maximum inhibition efficiency of 90.84% at 20% SiC content. The corrosion rates decreased at higher NaCl concentration, with maximum inhibition efficiency of 94.12 and 77.27% at 20% SiC. Alloy samples in 2 M H2 SO4 /0% NaCl at 0 and 20% SiC visibly decreased in OCP value over wide variation compared to samples with varying NaCl concentration due to loss of passivity. OCP values for alloys at varying NaCl concentration decreased over a very short variation due to repassivation. Statistical data showed silicon carbide to be the only relevant variable responsible for the corrosion rate values with F-values of 8.85 corresponding to a percentage significance of 54.8%. Optical images showed the presence of corrosion pits of smaller dimension, yet deeper on the morphology of the alloy without silicon carbide compared the alloy containing it, whose corrosion pits, seems wider but very shallow.